The J. Fodor's language of thought hypothesis and epistemic logic - Konstantin Rayhert (Cхід, 2016)
The study is to show the similarities between J. Fodor's Language of Thought hypothesis and epistemic modal logic. According to the J. Fodor's hypothesis there is the language of thought (also called "Mentalese") that is the meta-language in which mental representations of attitudes of organism to propositions expressed in object-language (for example: knowledge, belief, hope, desire, statement) are formulated. These attitudes are called "propositional attitudes". In the hypothesis propositional attitudes are thoughts and relations between organism and proposition. Propositional attitudes are of interest for epistemic modal logics. In epistemic logics propositional attitudes are relations considered as modalities, i.e. propositions with modal operators. On certain conditions J. Fodor's Language of Thought hypothesis may be considered as a sort of epistemic modal logic, only it would require certain updating as a formal logical system. The similarities between J. Fodor's Language of Thought and epistemic modal logics give two opportunities. First opportunity is to make special version of epistemic modal logic as an instrument of research for cognitive psychology based on J. Fodor's Language of Thought hypothesis. Second opportunity is to accept the idea of J. Fodor's Language of Thought as an innate language and to attain comprehension that epistemic modal logics are not especially constructed formal languages (formal systems) but innate cognitive programs. It might enable to extrapolate the idea of innate languages onto all formal languages including logical languages and to attempt verifying that idea experimentally within cognitive sciences.